Factor Analysis of the Trauma Symptoms Checklist for Children (TSCC) in Survivors of Childhood Sexual Abuse - Faizah, Rayinda; Hermahayu, Hermahayu (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This study aims to perform reliable analysis and factor analysis of the TSCC instrument to measure trauma in CSA survivors. This research method used the CFA technique while the sample of this study was 62 children with several criteria, namely aged 8 to 17 years, had a history of experiencing sexual violence in the previous two years, and were willing to participate in this study. The results of this study indicate that the CSA instrument is proven to be reliable with score 0.862 and the EFA results show that there are two factors formed. The first factor consists of post-traumatic stress, anxiety, dissociation and sexual concern which is called the neuroticism factor. The second factor consists of depression and anger which is called the depression factor. It is hoped that the results of this study will be able to provide a valid instrument for measuring trauma so that it can be applied to children who have experienced CSA so they can get the right intervention to heal their trauma.